MODEL PEMBELAJARAN INOVATIF DI ERA GLOBAL (Suatu Kajian Perbandingan di Negara Maju)* - Fuad Abdul Hamied (Khazanah Pendidikan, 2009)
This topic is important to discuss, at least as an effort to improve the quality of education. From this topic, we hopefully can get something practical which can be applied in the classroom. In the discussion of this matter, I will look back at the problem of education in Indonesia, then we try to find what problem globalization has caused, and finally we will discuss what technology is used in education and teaching. I also am going to discuss what policy has been or is being made by the government in relation with information and telecommunication technology. This discussion is closed with the one of the models which has been widely use in many developed and developing countries like Indonesia, the active learning model. Key words: innovative learning model, globalization era, active learning model.